2014
DOI: 10.1111/jgh.12419
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal eosinophilia and early satiety in functional dyspepsia: Confirmation of a positive association in an Australian cohort

Abstract: Duodenal eosinophilia occurs in a subset of FD. The potential role of duodenal eosinophils in FD has implications for diagnosis and therapeutic trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
123
5
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 45 publications
(99 reference statements)
10
123
5
9
Order By: Relevance
“…1) were increased in patients with functional dyspepsia and correlated with symptom intensity and impaired gastric emptying, suggesting that gastric disturbances in functional dyspepsia could, in fact, be secondary to duodenal inflammation 94 . Together with data of increased duodenal eosinophilia 90,91,95,96 , these studies have demonstrated that low-grade mucosal inflammation plays a key part in the pathogenesis of functional dyspepsia. Increased CD4 + T helper 2 (T H 2) cell response is a potent producer of key cytokines (IL-4, IL-5 and IL-13) that are involved in recruiting and activating eosinophils and mast cells 97 .…”
Section: Gastroduodenal Inflammationmentioning
confidence: 63%
“…1) were increased in patients with functional dyspepsia and correlated with symptom intensity and impaired gastric emptying, suggesting that gastric disturbances in functional dyspepsia could, in fact, be secondary to duodenal inflammation 94 . Together with data of increased duodenal eosinophilia 90,91,95,96 , these studies have demonstrated that low-grade mucosal inflammation plays a key part in the pathogenesis of functional dyspepsia. Increased CD4 + T helper 2 (T H 2) cell response is a potent producer of key cytokines (IL-4, IL-5 and IL-13) that are involved in recruiting and activating eosinophils and mast cells 97 .…”
Section: Gastroduodenal Inflammationmentioning
confidence: 63%
“…Observational studies show an increased number of eosinophils in duodenal biopsies obtained from adults and children with functional dyspepsia. [2][3][4] Other studies have shown an increase in mast cells in the mucosa and evidence of inflammation in the sub-mucosal nerves and ganglia in the upper gastrointestinal tract. …”
mentioning
confidence: 99%
“…S1 in the Supplementary Appendix). [36][37][38] Duodenal eosinophilia has been linked to smoking and to symptoms of early satiety and pain; barrier disruption and increased duodenal permeability have been documented. 36,39 In some cases, mast cells that can recruit eosinophils have also been observed in functional dyspepsia, but the patient population that was studied included patients with both functional dyspepsia and the irritable bowel syndrome.…”
mentioning
confidence: 99%
“…[36][37][38] Duodenal eosinophilia has been linked to smoking and to symptoms of early satiety and pain; barrier disruption and increased duodenal permeability have been documented. 36,39 In some cases, mast cells that can recruit eosinophils have also been observed in functional dyspepsia, but the patient population that was studied included patients with both functional dyspepsia and the irritable bowel syndrome. 39 Further evidence linking intestinal inflammation to functional dyspepsia is provided by the finding of enhanced small-bowel homing T lymphocytes that are positive for both α 4 β 7 integrin and chemokine receptor 9 in patients with functional dyspepsia -a finding that has been significantly associated with the release of cytokines (including tumor necrosis factor α), a greater severity of symptoms, and delayed gastric emptying, 40 thus implicating the duodenum in gastric disorders.…”
mentioning
confidence: 99%